Nutritional Quality And Fiber Fraction Of Complete Feed Silage Based On Sago By-Products, Imperata Cylindrica And Leucaena Leucocephala - Insun sangadji sangadji (Buletin Peternakan, 2020)
This experiment aimed to know nutrition quality and fiber fraction of complete feed silage based on sago by-products, Imperata cylindrica, and Leuchaena leucocephala in different compositions which fermented for three weeks. The study was conducted at the Laboratory of Feed Engineering and Technology, Faculty of Agriculture, University of Pattimura which lasted for three months. The main ingredients used to make silage complete ration in this study consisted of sago pulp, reeds, lamtoro, concentrate and plus coconut water. Complete ration silage fermented using coconut water plus which is a mixture of urea 95% and coconut water 5%. This research conducted by using randomized complete design with five factors of silage compound that are P0 = 60% forages + 40% concentrate (for control) ; P1 = 10% sago by-products + 40% Imperata cylindrical + 10% Leucaena Leucocephala + 40% concentrate ; P2 = 20% sago by-products + 30% Imperata cylindrica + 20 % Leucaena Leucocephala + 30% concentrate ; P3 = 30 % sago by-products + 20% Imperata cylindrica + 30 % Leucaena Leucocephala + 20% consentrate ; dan P4 = 40% sago by-products + 10%  Imperata cylindrica + 40% Leucaena Leucocephala + 10% concentrate. Each treatment used four replicates. The variable observed were the percentage of water content, ash, crude protein, crude fat, crude fiber, NDF, ADF, and lignin. The results showed that sago by-products, Imperata cylindrica and Leuchaena leucocephala can be used for basic materials of complete feed silage in ruminants feed because they have no difference quality of nutrition and fiber fraction compared with control P0.